DOSAGE EFFECTIVENESS OF MANURE AND PLANTING DISTANCE ON THE GROWTH AND PRODUCTION OF PEANUTS (ARACHIS HYPOGAEA, L) - Hardjoloekito, Hari Soeseno (International Journal of Research -GRANTHAALAYAH, 2020)
This study aims to identify and study the effect of plant spacing and chicken manure fertilizers on growth and yield of peanut. This research was conducted at the Experimental Farm of the Faculty of Agriculture Land Dictionary Universitas Soerjo Ngawi, East Jawa , took place from Desember 2019 to March 2020 .The method used is a plot design Separated (Split Plot Design) with nine combinations of treatments and three replications. The main plot (main plot) is a spacing (A), J1 20 cm x 20 cm, 30 cm x 20 J2 cm, J3 40 cm x 20 cm, as a subplot (sub-plots) is the dose of compost (P), P1 5 tons / ha, P2 10 tons / ha, P3 15 tons / ha. Parameters observed that plant height (cm), number of primary branches (branch), the overall weight of pod (g), number of pods containing (pod), the number of empty pods (legumes), berangkasan wet weight (g), dry berangkasan weight (g ), 100 seed weight (g).Based on the results of analysis of variance showed that the spacing of chicken manure fertilizer rate and not significant for all variables observed. Treatment interaction effect was not significant on all observed variables, but the variables significantly.